PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR SISWA PADA TEMA DAERAH TEMPAT TINGGALKU - Irma Hutauruk; Rumiris Lumban Gaol; Saut Maulahe; Darinda Sofia Tanjung (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The students’ low learning outcome was caused by both internal and external factors. The internal factors included a lack of interest and talents of the students and a lack of motivation from parents and the environment so that students were not enthusiastic about carrying out teaching and learning activities in their education. Meanwhile, the external factors could be seen from the learning strategy, the management of learning activities, and less varied methods and learning models. The external factors were also observed from the lack of other sources to assist the teaching and learning process at schools. Therefore, researchers initiated to find a solution for these problems. Contextual Teaching and Learning (CTL) model was one of the interactive learning models that teachers could implement in the learning process. This model can draw students' real and clear understanding of the learning process they follow. The objectives of this research were to find out the influence of CTL Model on the students’ learning outcomes on the theme of “Daerah Tempat Tinggalku” at grade IV SD Negeri 091332 Raya Bayu. This research was the experimental research. The data were analyzed by the correlation coefficient test and T test. The results showed that the average pretest score in the experimental class was 58.5 and the average posttest score in the experimental class was 86.9. This was supported by the results of the correlation coefficient test which was 0.781, meaning (0.781) >. (0.361). Thus, Ha was accepted. This implied that there was a significant influence of Contextual Teaching and Learning (CTL) Model on the students’ learning outcomes at grade IV-A SD Negeri 091332 Raya Bayu. The results of t-test also revealed 6,621 > 1,701, meaning that the hypothesis Ha was accepted. This confirmed that Contextual Teaching and Learning (CTL) model significantly influenced the students’ learning outcomes on the theme of “Daerah Tempat Tinggalku” at grade IV-A SD Negeri 091332 Raya Bayu the academic year 2019/2020.